Investigations on Regulation of MicroRNAs in Rice Reveal [Ca2+]cyt Signal Transduction Regulated MicroRNAs - Kansal, Shivani; Panwar, Vaishali; Mutum, Roseeta Devi; Raghuvanshi, Saurabh (Frontiers in Plant Science, 2021)
MicroRNAs (miRNAs) are critical components of the multidimensional regulatory networks in eukaryotic systems. Given their diverse spectrum of function, it is apparent that the transcription, processing, and activity of the miRNAs themselves, is very dynamically regulated. One of the most important and universally implicated signaling molecules is [Ca2+]cyt. It is known to regulate a plethora of developmental and metabolic processes in both plants and animals; however, its impact on the regulation of miRNA expression is relatively less explored. The current study employed a combination of internal and external calcium channel inhibitors to establishing that [Ca2+]cyt signatures actively regulate miRNA expression in rice. Involvement of [Ca2+]cyt in the regulation of miRNA expression was further confirmed by treatment with calcimycin, the calcium ionophore. Modulation of the cytosolic calcium levels was also found to regulate the drought-responsive expression as well as ABA-mediated response of miRNA genes in rice seedlings. The study further establishes the role of calmodulins and Calmodulin-binding Transcription Activators (CAMTAs) as important components of the signal transduction schema that regulates miRNA expression. Yeast one-hybrid assay established that OsCAMTA4 & 6 are involved in the transcriptional regulation of miR156a and miR167h. Thus, the study was able to establish that [Ca2+]cyt is actively involved in regulating the expression of miRNA genes both under control and stress conditions.